EFFECTIVENESS OF USING THE HATFIELD SYSTEM IN THE TRAINING PROCESS (Physical Culture and Sport: Scientific Perspective, 2025)
Strength training is one of the key components of the training process in powerlifting, and the search for effective methods to develop strength and minimize the risk of injuries is a relevant area of sports science. The Hatfield System, developed by Dr. Fred Hatfield, combines traditional strength exercises with additional hand support, allowing athletes to lift heavier weights and enhance overall strength. Despite its widespread use in strength sports, the scientific justification and effectiveness of this method in powerlifting training remain insufficiently studied. This study conducted a comparative analysis of the effectiveness of the Hatfield System and weekly undulating periodization (WUP) in developing strength performance in powerlifters. Participants were divided into two groups: one trained using the Hatfield System, while the other followed the WUP method. The training programs lasted six weeks and included the same overall training volume. The results showed that both methods contributed to a significant increase in strength in key powerlifting exercises (squat, bench press, and deadlift). At the same time, no significant changes in anthropometric indicators were observed, confirming their effectiveness in sports where strength gains are required without increasing body mass. The Hatfield System was found to be more structured, while WUP allowed for greater variability in load distribution. Despite the positive results, the study has some limitations that should be considered: еxperiment duration (6 weeks) – longer studies are needed to evaluate long-term effects. Small sample size (n=22) – larger-scale studies are necessary for more generalized conclusions. Practical recommendations suggest adapting both methods based on individual athlete needs. Future research perspectives include investigating the long-term effects of the Hatfield System, its impact on injury prevention, and biomechanical aspects of strength training execution.
Keywords: exercises; training effectiveness; maximal strength; injury prevention; strength training; Hatfield System; weekly undulating periodization; physical conditioning